KADAR THIAMIN HIDROKLORIDA (VITAMIN B1) PADA NASI BERAS PUTIH DAN BERAS MERAH PADA BERBAGAI WAKTU PENYIMPANAN PADA ALAT MAGIC-COM - Mayun Laksmiwati, A. A. I. A.; Ratnayani, Ketut; Agustini, Ni Wayan (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012, 2012)
This paper discusses the influence of storage time on the thiamine hydrochloride content in rice. White rice (C36) and red rice were stored in a magic-com for a period of time, of 0 hours, 6 hours and 12 hours. Thiamine hydrochloride contents in rice were separated with the use of a chromatography column with alumina oxide, while and the measurement was carried out by UV-Vis spectrophotometry. It was found that the thiamine hydrochloride content in red rice stored within 0 hours, 6 hours and 12 hours were, 5.3 mg/kg, 4.5 mg/kg and 2.8 mg/kg, respectively, while in white rice they were found to be 2.6 mg/kg, 2.0 mg/kg and 1.4 mg/kg, respectively.
Keywords: thiamine hydrocloride, red rice and white rice